2020
DOI: 10.1097/sla.0000000000003580
|View full text |Cite
|
Sign up to set email alerts
|

The American Association of Endocrine Surgeons Guidelines for the Definitive Surgical Management of Thyroid Disease in Adults

Abstract: Objective: To develop evidence-based recommendations for safe, effective, and appropriate thyroidectomy. Background: Surgical management of thyroid disease has evolved considerably over several decades leading to variability in rendered care. Over 100,000 thyroid operations are performed annually in the US. Methods: The medical literature from 1/1/1985 to 11/9/2018 was reviewed by a panel of 19 experts in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
388
2
52

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 345 publications
(446 citation statements)
references
References 995 publications
4
388
2
52
Order By: Relevance
“…The extent of lymph node dissection at the time of thyroidectomy is an ongoing discussion. Because the central node compartment is the site of primary lymphatic drainage from the thyroid, and LNM occurs during the early course of MTC [ 20 , 21 ], the guidelines of the ATA/European Thyroid Association (ETA), the British Thyroid Association (BTA), and the American Association of Endocrine Surgeons (AAES) recommend central node compartment dissection regardless of unequivocal evidence of cervical LNM [ 9 , 16 , 22 ]. However, the NCCN guidelines recommend total thyroidectomy with cervical dissection for primary tumors greater than 1.0 cm in diameter or bilateral thyroid disease [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The extent of lymph node dissection at the time of thyroidectomy is an ongoing discussion. Because the central node compartment is the site of primary lymphatic drainage from the thyroid, and LNM occurs during the early course of MTC [ 20 , 21 ], the guidelines of the ATA/European Thyroid Association (ETA), the British Thyroid Association (BTA), and the American Association of Endocrine Surgeons (AAES) recommend central node compartment dissection regardless of unequivocal evidence of cervical LNM [ 9 , 16 , 22 ]. However, the NCCN guidelines recommend total thyroidectomy with cervical dissection for primary tumors greater than 1.0 cm in diameter or bilateral thyroid disease [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic lateral node dissection is more controversial. The preoperative serum calcitonin level and ultrasound findings can be helpful for determining the need for lateral node dissection [ 9 , 16 ]. Machens et al reported preoperative serum calcitonin levels based on the pathologic extent of disease [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ongoing evolution of these tests, combined with academic, clinical, and commercial interests, suggests that these molecular tests are now firmly part of the diagnostic armamentarium for thyroid nodules. Indeed, medical societal guidelines have continued to include discussion on molecular testing as diagnostic adjuncts for indeterminate thyroid nodules ( 1 3 , 14 16 ).…”
Section: Molecular Marker Panelsmentioning
confidence: 99%